Analysis of Da'wah Science and Islam in Educating Ummah by Dr. Zakir Naik through Islamic Communication in Internet Videos - Anwar, Ikbalul (Darul Yasin Al Sys, 2023)
Internet video is a new form of media that allows us to study the movement of narratives. Lectures discussing Islam and science often appear in this video. One of the most popular speakers in this material is Dr. Zakir Naik, a Muslim preacher from India. Dr Zakir Naik's lectures often interpret certain modern scientific discoveries to prove the divine origin of the Qur'an, Dr. Zakir Naik also uses material from the lecture